Motor skills and school performance in children with daily physical education in school - a 9-year intervention study - Ericsson, I.; Karlsson, M. K. (Scandinavian Journal of Medicine & Science in Sports, 2014)
The aim was to study long-term effects on motor skills and school performance of increased physical education (PE). All pupils born 1990-1992 from one school were included in a longitudinal study over nine years. An intervention group (n = 129) achieved daily PE (5 × 45 min/week) and if needed one extra lesson of adapted motor training. The control group (n = 91) had PE two lessons/week. Motor skills were evaluated by the Motor Skills Development as Ground for Learning observation checklist and school achievements by marks in Swedish, English, Mathematics, and PE and proportion of pupils who qualified for upper secondary school. In school year 9 there were motor skills deficits in 7% of pupils in the intervention group compared to 47% in the control group (P < 0.001), 96% of the pupils in the intervention group compared to 89% in the control group (P < 0.05) qualified for upper secondary school. The sum of evaluated marks was higher among boys in the intervention group than in the control group (P < 0.05). The sum of marks was also higher in pupils with no motor skills deficit than among pupils with motor skills deficits (P < 0.01), as was the proportion of pupils who qualified for upper secondary school (97% vs 81%, P < 0.001). Daily PE and adapted motor skills training during the compulsory school years is a feasible way to improve not only motor skills but also school performance and the proportion of pupils who qualify for upper secondary school.